Noninvasive Imaging of Aortic Atherosclerosis by Ultrasound Biomicroscopy in a Mouse Model. (1st January 2015) - Zhang, Xiaoshan; Ha, Si; Wei, Wei; Duan, Shasha; Shi, Yilu; Yang, Ya
Abstract : Objectives: The noninvasive and accurate evaluation of vessel characteristics in mouse models has become an intensive focus of vascular medicine. This study aimed to apply ultrasound biomicroscopy to evaluate aortic atherosclerotic progression in a low‐density lipoprotein receptor (LDL‐R) knockout mouse model of atherosclerosis. Methods: Ten male LDL‐R −/− C57BL/6 mice aged 16 and 24 weeks and 8 male wild‐type C57BL/6 mice aged 16 and 24 weeks were used as experimental and control groups, respectively. Ultrasound biomicroscopy was applied to detect the morphologic characteristics of the aortic root, ascending aorta, aortic arch, and carotid artery and to measure the aortic root intima‐media thickness and carotid artery bifurcation. Results: Ultrasound biomicroscopy showed a significant increase in the aortic root intima‐media thickness from 0.10 ± 0.03 mm in 16‐week‐old mice to 0.16 ± 0.04 mm in 24‐week‐old mice ( P < .01). The ultrasound biomicroscopically measured intima‐media thickness was highly correlated with the histologic measurement ( r = 0.81). Conclusions: Ultrasound biomicroscopy could be used for a noninvasive, accurate, and dynamic analysis of aortic atherosclerosis in LDL‐R knockout mice.